Epilepsia e trabalho: aspectos biopsicossociais da qualidade de vida - Golfetto, Vando (2018)
Epilepsy is a common, chronic neurological condition that affects 1% to 3% of the world’s population and its diagnosis is associated with a high incidence of psychosocial difficulties. This study focuses on understanding the biopsychosocial factors emerging during subjectivation of individuals with epilepsy, specifically with regard to the labor market. This study is based on a sample from the records of people with epilepsy in the 20 th regional health department (20ª Regional de Saúde), located in the municipality of Toledo (PR). We utilized a quantitative approach to address the research question. Specifically, we took used a data collection form including questions regarding sociodemographic characteristics and the Subjective Handicap Of Epilepsy (SHE) scale. The first production of this dissertation discusses the perceptions associated with epilepsy and, in particular, the relationships between epilepsy and working life. For this purpose, historical and conceptual studies are reviewed in order to better understand how epilepsy was viewed in Western society before scientific knowledge was obtained. Since the pre-modern mystic and religious discourse was rejected, epilepsy has been considered a condition belonging to medical science and given the status of an organic disease; however, the stigma, which was previously instigated by obscure interpretations, has not disappeared. Technical arguments based on the perspective of risk and safety of those involved lead to conditions that restrict working life, an interpretation that has been scrutinized in academic circles through discourse that aims to preserve personal autonomy in patients affected by epilepsy. It is necessary to preserve the plurality of points of view in order to ensure that the ethical subject and law subsist alongside the patient, and where technical knowledge can result in better life experiences without affecting the working chances of the affected individuals. The objective of the second production of the study was to assess incapacity of individuals with epilepsy, particularly with regard to biopsychosocial aspects, using the SHE scale. The results were consistent across the studied population, and the findings reproduce those of the original study for the validation of the protocol in Brazil; we observed agreement between the results and the original studies across the six key domains (physical, social and personal, change, satisfaction with life, self-perception, and work and activities). The analyses developed in the present study using SHE indicate factors related to the crises themselves, stigmas, and psychosocial variables such as low self-esteem, difficulties in dealing with adverse situations, and low effectiveness at work.